METHODOLOGY FOR CORRECTION OF STUDENTS’ PHYSICS KNOWLEDGE IN CONDITIONS OF EDUCATIONAL LOSSES - Кузнєцова, Олена; Коломоєць, Ганна (SWorldJournal, 2025)
In the conditions of war, our country has suffered significant educational losses that have long-term consequences. An analysis of the results of the NMT in physics in 2023-2024 showed a significant decrease in the qualitative level of knowledge and motiv